Civil societybrief Timor-Leste. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Improving civil society capacity in Timor-Leste has been a focus of numerous local and international development efforts for some years. As a result, today in Timor-Leste, a number of reliable, robust, and credible civil society organizations (CSOs) work both independently and with development partners. The capacity of Timor-Leste CSOs has increased since the restoration of independence, particularly among Dili based CSOs, but major sustainability and operational challenges remain for the civil society sector in Timor-Leste as donor funds tighten.
Keywords: Public administration -- Asia; Economics; Electronic book